Automatically gated image-guided breath-hold IMRT is a fast, precise, and dosimetrically robust treatment for lung cancer patients - Simeonova-Chergou, Anna; Jahnke, Anika; Siebenlist, Kerstin; Stieler, Florian; Mai, Sabine; Boda-Heggemann, Judit; Wenz, Frederik; Lohr, Frank; Jahnke, Lennart (Strahlentherapie und Onkologie, 2016)
Background: High-dose radiotherapy of lung cancer is challenging. Tumors may move by up to 2 cm in craniocaudal and anteroposterior directions as a function of breathing cycle. Tumor displacement increases with treatment time, which consequentially increases the treatment uncertainty. Objective: This study analyzed whether automatically gated cone-beam-CT (CBCT)-controlled intensity modulated fast deep inspiration breath hold (DIBH) stereotactic body radiation therapy (SBRT) in flattening filter free (FFF) technique and normofractionated lung DIBH intensity-modulated radiotherapy (IMRT)/volumetric-modulated arc therapy (VMAT) treatments delivered with a flattening filter can be applied with sufficient accuracy within a clinically acceptable timeslot. Materials and methods: Plans of 34 patients with lung tumors were analyzed. Of these patients, 17 received computer-controlled fast DIBH SBRT with a dose of 60 Gy (5 fractions of 12 Gy or 12 fractions of 5 Gy) in an FFF VMAT technique (FFF-SBRT) every other day and 17 received conventional VMAT with a flattening filter (conv-VMAT) and 2-Gy daily fractional doses (cumulative dose 50-70 Gy).ResultsFFF-SBRT plans required more monitor units (MU) than conv-VMAT plans (2956.6 ± 885.3 MU for 12 Gy/fraction and 1148.7 ± 289.2 MU for 5 Gy/fraction vs. 608.4 ± 157.5 MU for 2 Gy/fraction). Total treatment and net beam-on times were shorter for FFF-SBRT plans than conv-VMAT plans (268.0 ± 74.4 s vs. 330.2 ± 93.6 s and 85.8 ± 25.3 s vs. 117.2 ± 29.6 s, respectively). Total slot time was 13.0 min for FFF-SBRT and 14.0 min for conv-VMAT. All modalities could be delivered accurately despite multiple beam-on/-off cycles and were robust against multiple interruptions. Conclusion: Automatically gated CBCT-controlled fast DIBH SBRT in VMAT FFF technique and normofractionated lung DIBH VMAT can be applied with a low number of breath-holds in a short timeslot, with excellent dosimetric accuracy. In clinical routine, these approaches combine optimally reduced lung tissue irradiation with maximal delivery precision for patients with small and larger lung tumors.
Gesehen am 15.03.2019